Pengaruh Kepribadian terhadap Keputusan Pembelian Konsumen Produk Kahf pada Mahasiswa FISIP USU - Risliza Hutabarat, Eka; Ayman Ashari, Muhammad; Vincentius Naibaho, Robert; Sitorus, Sabrina; Muda Panjaitan, Yasser (PT. Alahyan Publisher Sukabumi, 2024)
In the digital age, consumer personality influences purchase decisions. This study analyzes the influence of five personality dimensions (agreeableness, conscientiousness, extraversion, neuroticism, and openness) on the purchase decision of Kahf products on FISIP USU students. Using a quantitative approach and involving 150 respondents, the results showed that only conscientiousness had a positive and significant effect on purchase decisions. Other personality dimensions did not show significant influence. This research contributes to understanding how personality dimensions affect consumer purchasing decisions, especially among students. The results can be used by companies to devise more effective marketing strategies by considering the personality characteristics of consumers. These findings suggest that companies focus more on marketing that matches the characteristics of conscientiousness to improve purchasing decisions.